The ALARIC parton shower - Reichelt Daniel (EPJ Web of Conferences)
Parton showers are important tools in the event generation chain for present and future colliders. Recently, their formally achieved accuracy has been under extended scrutiny. This contribution will present a novel take on dipole parton showers, resulting in the design of a new parton shower called ALARIC that is implemented in the SHERPA framework. Its resummation properties, including analytic and numerical proofs of its NLL accuracy, will be discussed alongside the latest developments.